ANALYSIS OF LEARNING STRATEGIES IN SPEAKING ENGLISH AT THE TENTH GRADE STUDENTS OF SMA NEGERI 1 MANIAMOLO - Ries Clara Alverin Zagoto (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
This study dealt some students in tenth grade have a wide variety and uniqueness in speaking English. The purpose of this study is to find out the learning strategies in speaking English. This research used qualitative research. The data was taken from questionnaire filled out by students. The data source is the tenth grade Cut Nyak Dien class students of SMA Negeri 1 Maniamolo Academic Year 2023/2024. The researcher used questionnaire of strategy inventory of language learning (SILL) and interview to collect data of the research. The finding shows that, language learning strategies based on six strategies divided into memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies and social strategies. The content component with an average score and rating qualities cognitive strategies 4.91, metacognitive strategies 3.15, and memory strategies 3.14 including high and medium level used by students. Component with an average score compensation strategies 2.09, affective strategies 2.10 and social strategies 2.10 including low level used by students. From the result of the data, only 3 learning strategies are classified as a dominant used by students. Lastly, the result of data analysis of students learning strategies in speaking English tenth grade cut nyak dien class students of SMA Negeri 1 Maniamolo used cognitive strategies, metacognitive strategies and memory strategies in speaking English. It is suggested that can applied are learning strategy appropriately for themselves in speaking.